Utilization of Lemongrass as a Raw Material for Hand Sanitizer Production to Enhance Community MSMEs in Nagari Sipinang Post-Disaster: Value-Added Processing of Lemongrass (Cymbopogon citratus) into Hand Sanitizer Products to Support Post-Disaster MSME Empowerment in Nagari Sipinang, Agam Regency - Dillasamola, Dwisari; Aldi, Yufri; Sari, Silvia Permata; Ramadhani, Kesha Fadhiilah; Airinisa, Salsa Dwi; Fuadiyah, Alda; Amanda, Diva; Nabila, Alya Puti Dwi; Ramadhan, Fadli Pratama; Dzaki, Muhammad; Syakira, Azya Hana; Irianti, Dira Adhani; Defani, Nabillah Puteri (Jurnal Hilirisasi IPTEKS, 2026)
The significantly disrupted socio-economic conditions in Nagari Sipinang, Agam Regency, particularly through the degradation of agricultural land and reduced household income. This study aimed to evaluate a community-based, value-added intervention utilizing lemongrass (Cymbopogon citratus) as a raw material for hand sanitizer production to support post-disaster recovery and micro, small, and medium enterprise (MSME) development. A quasi-experimental community empowerment design was employed, involving 30 participants selected through purposive sampling. The intervention consisted of structured educational sessions on post-disaster hygiene risks, hands-on training in aqueous-ethanolic extraction of lemongrass, and technical assistance in formulation and packaging. Pre- and post-intervention assessments were conducted to measure changes in knowledge, skills, and production capacity. Product evaluation included organoleptic testing and pH analysis using standardized procedures. The results demonstrated a significant improvement in participants’ competencies, with mean knowledge and skill scores increasing by 80% (p < 0.05). Additionally, one community-based MSME unit was successfully established, producing hand sanitizer at a small commercial scale. The formulated product exhibited acceptable organoleptic properties, including a characteristic fresh aroma, and maintained a stable pH of 5.5, consistent with topical safety standards. In conclusion, the downstream utilization of lemongrass represents a scientifically grounded and economically viable strategy for enhancing community resilience. This approach not only contributes to post-disaster public health mitigation but also facilitates sustainable MSME revitalization in Nagari Sipinang.